Application of microfiltration in water and wastewater treatment - Chen, Chilung; Vigneswaran, Saravanamuthu; I, Fude; Yamamoto, Kazuo; Kriengsak Udomsinrot; China Technical Consultants Inc. Republic of China (Bangkok : Asian Institute of Technology, 1988)
The cross-flow membrane filtration techniques like ultrafiltration (UF) and microfiltration (MF) are useful in removing macromolecules, colloids and suspended solids. Unlike in standard filtration techniques, in cross-flow filtration, since the direction of the feed flow is tangential to the filter surface, accumulation of the filtered solids on the filter medium can be minimized by shearing action of flow. This study was divided into two parts: a) water treatment and b) wastewater treatment by using microfiltration technique. In water treatment, a study was c9nducted to determine the efficiency of MF as disinfecting unit and its applicability in the disinfection process of water treatment system. It was found out that correct choice of membrane size could achieve 100% E.Coli removal efficiency. Similarly, study performed showed that correct choice of cross-flow velocity and transmembrane pressure are very essential in the techno-economical optimization of this process. In wastewater treatment, AIT sewage was used as wastewater to be treated. A pretreatment using on-line flocculation arrangement can further improve the performance, while leading to a significant increase in permeate flux. Thus, in this study the possibility of using MF unit (with on-line flocculation arrangement) as household sewage treatment was investigated. It was found out that correct choice of membrane size, alum dose and crossflow velocity were very important. This treatment achieved not only high COD removal but also very high color and E.Coli removal. Experiments were conducted with various kinds of membrane pore sizes, different suspensions and different operating parameters like cross flow velocity, pressure difference etc.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Water -- Purification -- Filtration; Sewage -- Purification -- Filtration